Acceptance level of Islamic banking among non-muslims students at UiTM Puncak Alam campus / Nurul Marhaini Mahazer. - Mahazer, Nurul Marhaini (2019)
The knowledge of Islamic banking is very important among customers especially non-Muslim customers. This is because of the lack of knowledge and awareness will make them less interested in offering services that has been provided by Islamic banking. In addition, knowledge and awareness of Islamic banking will help to change the perception of non-Muslim customers in the Islamic banking system and increasing the acceptance among non-Muslim customers and also attract customers to use Islamic banking services. Therefore, this study focuses on the understanding, factor influence and the acceptance of Islamic banking among non-Islamic students at UiTM Puncak Alam Campus. The results of this study will show the understanding, influencing factors and acceptance among non-Muslim customers have positive or negative results.